2012
DOI: 10.1002/asia.201101017
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of “Non‐Symmetrical” 1,2,4‐Trithiolanes with [(phosphane)Pt02‐nbe)] Complexes

Abstract: Two unsymmetrical 1,2,4-trithiolanes (1d and 1e) were reacted with [Pt(0)(PPh(3))(2)(η(2)-nbe)] (6; nbe=norborn-2-ene) and [Pt(0)(dppn)(η(2)-nbe)] (11; dppn=1,8-bis(diphenylphosphanyl)naphthalene)), respectively. Their treatment with compound 6 resulted in the formation of six-membered platinacycles of type 7, which selectively underwent fragmentation into dithiolato complexes and thiobenzophenone (4b). The isolation of the first stable C-substituted member of this class of compounds (i.e., compound 7e) permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In addition, platinathiirane 3d was prepared from thiobenzophenone ( 1b ) and 2c . Three of the four complexes 3a – d have been characterized using XRD methods revealing that the bond lengths in the platinathiirane rings correspond to the data reported for similar platinaheterocycles derived from several aryl and cycloaliphatic thioketones [16,17,18,47]. Compounds 3a – d were characterized electrochemically using CV.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, platinathiirane 3d was prepared from thiobenzophenone ( 1b ) and 2c . Three of the four complexes 3a – d have been characterized using XRD methods revealing that the bond lengths in the platinathiirane rings correspond to the data reported for similar platinaheterocycles derived from several aryl and cycloaliphatic thioketones [16,17,18,47]. Compounds 3a – d were characterized electrochemically using CV.…”
Section: Discussionsupporting
confidence: 52%
“…Subsequent (3 + 2)-cycloelimination of the intermediate formed thereby, releases the corresponding thioketone which in the next step interacts with another equivalent of 2 forming platinathiiranes 3 . In these multi-step reactions, the second type of products formed, was identified as four membered (dithiolato)platinum(II) complexes 4 [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, cycloreversion proved a successful strategy for studying the sulfur analogue, thioformaldehyde S -sulfide (CH 2 SS; 2b in Figure ). Indeed, Maier and co-workers showed via matrix isolation that the thermal fragmentation of 1,2,4-trithiolane ( 2a ), a stable substance that is common in nature, yields CH 2 SS ( 2b ) and the companion product dithiirane (H 2 CS 2 ; 2c in Figure ) in a ratio of 1:2.5. Complete conversion to 2c was achieved photochemically through irradiation of the product mixture with visible light (λ > 570 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies performed with differently substituted 1,2,4‐trithiolanes demonstrated that the “dithiirane mechanism” shown in Scheme has to be replaced by the alternative ring‐expansion of the starting 1,2,4‐trithiolane 1 resulting in the formation of six‐membered Pt‐heterocycles 22 , which undergo thermal decomposition with release of the corresponding thioketone, which is subsequently trapped by another bisphosphane Pt(0) complex, (Scheme ). The postulated six‐membered intermediate formed from 1n and (Ph 3 P) 2 Pt(η 2 ‐nbe) is stable at room temperature, and its structure was confirmed not only spectroscopically but also by X‐ray crystallography …”
Section: Coordination Chemistry Of 124‐trithiolanesmentioning
confidence: 87%